Dual Inoculation With Arbuscular Mycorrhizal Fungi and Phosphorus Solubilizing Fungi Synergistically Enhances the Mobilization and Plant Uptake of Phosphorus From Meat and Bone Meal - Jatana, Bhupinder Singh; Kitchens, Christopher; Ray, Christopher; Gerard, Patrick; Tharayil, Nishanth (Frontiers in Soil Science, 2021)
Phosphorus (P) is the second most important mineral nutrient for plant growth and plays a vital role in maintaining global food security. The natural phosphorus reserves (phosphate rock) are declining at an unprecedented rate, which will threaten the sustainable food supply in near future. Rendered animal byproducts such as meat and bone meal (MBM), could serve as a sustainable alternative to meet crop phosphorus demand. Even though nitrogen (N) from MBM is readily mineralized within a few days, >75% of the P in MBM is present as calcium phosphate that is sparingly available to plants. Thus, application of MBM with the aim of meeting crop N demand could result in buildup of P reserves in soil, which necessitates the need to improve the P mobilization from MBM to achieve higher plant P use efficiency. Here we tested the potential of two microbial inoculum- arbuscular mycorrhizal fungi (AMF) and P solubilizing fungi (Penicillium bilaiae), in improving the mobilization of P from MBM and the subsequent P uptake by maize (Zea mays). Compared to the non-inoculated MBM control, the application of P. bilaiae increased the P mobilization from MBM by more than 2-fold and decreased the content of calcium bound P in the soil by 26%. However, despite this mobilization, P. bilaiae did not increase the tissue content of P in maize. On the other hand, AMF inoculation with MBM increased the plant root, shoot biomass, and plant P uptake as compared to non-inoculated control, but did not decrease the calcium bound P fraction of the soil, indicating there was limited P mobilization. The simultaneous application of both AMF and P. bilaiae in association with MBM resulted in the highest tissue P uptake of maize with a concomitant decrease in the calcium bound P in the soil, indicating the complementary functional traits of AMF and P. bilaiae in plant P nutrition from MBM. Mycorrhizal fungi inoculation with MBM also increased the plant photosynthesis rate and root phosphomonoesterase activity. Collectively, our results demonstrate that P mobilization and uptake efficiency from MBM could be improved with the combined use of AMF and Penicillium bilaiae.